About the reserve army of labor in the Dependency Theory - Felix, Gil (2022)
Ruy Mauro Marini in “Dialectica de la dependencia” (1973) and in complementary articles published by the author. Since the revisit to these texts, it analyzes how this concept was inserted in its theoretical scheme and explicit what processes were the ones by which he attributed specificity to it within the so-called Marxist dependency theory. In conclusion, it indicates the centrality of this topic in Marini's theory and proposes an attentive approach to this premise for researchers who analyze the super-exploitation of labor currently based on its theoretical legacy.